Looking at Agenda 2063 (Ökologisches Wirtschaften - Fachzeitschrift, 2021)
How does a continent plan for its future? When the African Union convened for its 24th Ordinary Assembly in 2015, they created a blueprint. Agenda 2063 is both a plan for development and a snapshot of how Africa should be by 2063. But is it realistic, and most importantly, will it work?